Acute ischaemic stroke interventions: large vessel occlusion and beyond. Issue 1 (28th November 2019) - Sweid, Ahmad; Hammoud, Batoul; Ramesh, Sunidhi; Wong, Daniella; Alexander, Tyler D; Weinberg, Joshua Harrison; Deprince, Maureen; Dougherty, Jaime; Maamari, Dimitri Jean-Mickael; Tjoumakaris, Stavropoula; Zarzour, Hekmat; Gooch, Michael R; et al.
Abstract : Care for acute ischaemic stroke is one of the most rapidly evolving fields due to the robust outcomes achieved by mechanical thrombectomy. Large vessel occlusion (LVO) accounts for up to 38% of acute ischaemic stroke and comes with devastating outcomes for patients, families and society in the pre-intervention era. A paradigm shift and a breakthrough brought mechanical thrombectomy back into the spotlight for acute ischaemic stroke; this was because five randomised controlled trials from several countries concluded that mechanical thrombectomy for acute stroke offered overwhelming benefits. This review article will present a comprehensive overview of LVO management, techniques and devices used, and the future of stroke therapy. In addition, we review our institution experience of mechanical thrombectomy for posterior and distal circulation occlusion.